2012
DOI: 10.1111/j.1742-4658.2012.08534.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential requirements of mammalian ESCRTs in multivesicular body formation, virus budding and cell division

Abstract: The endosomal sorting complexes required for transport (ESCRTs) mediate membrane fission from the cytoplasmic face of the bud neck. ESCRTs were originally identified as factors involved in multivesicular body vesicle biogenesis in yeast but have since been shown to function in other membrane fission events in mammalian cells, including enveloped virus budding and the abscission step of cytokinesis. Several recent studies have revealed that not all ESCRT factors are required for each of these biological process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 68 publications
0
44
1
Order By: Relevance
“…6) In PTAPsequence-dependent virus budding of HIV-1, single depletion of VPS37B or VPS37C by siRNA causes modest inhibition of virus release. In contrast, when both VPS37B and VPS37C are depleted, virus release is dramatically inhibited.…”
Section: Diversity Of Escrt-i Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…6) In PTAPsequence-dependent virus budding of HIV-1, single depletion of VPS37B or VPS37C by siRNA causes modest inhibition of virus release. In contrast, when both VPS37B and VPS37C are depleted, virus release is dramatically inhibited.…”
Section: Diversity Of Escrt-i Complexesmentioning
confidence: 99%
“…4,5) The ESCRT system has additional roles including budding of enveloped RNA viruses from the plasma membrane and midbody abscission during cytokinesis in humans. 6) ESCRT machineries are composed of four protein complexes, termed ESCRT-0, -I, -II, and -III. ESCRT-I is a heterotetrameric complex containing the TSG101, VPS37, VPS28 and MVB12 proteins (see Fig.…”
mentioning
confidence: 99%
“…TSG101 is a component of ESCRT-I and ALIX is a binding protein of CHMP4, a component of ESCRT-III. [13][14][15] Although ALIX has a binding site for TSG101, we have reported that the weak ALIX-TSG101 interaction is potentiated by ALG-2, which bridges the two proteins and functions as a Ca 2þ -dependent adaptor protein. 16) The currently known interaction network of ESCRTs, ALIX, and ALG-2 is shown in Supplemental Fig.…”
Section: Alg-2 Is An Ef-hand-type Camentioning
confidence: 99%
“…Active Vps4 forms a hexameric complex that disassembles ESCRT-III, allowing recycling of its components, and also plays an active role in scission of the vesicle neck (Adell et al, 2014;Cashikar et al, 2014;Lata et al, 2008;Monroe et al, 2014;Mueller et al, 2012). In addition to their endocytic functions, ESCRT proteins, including Vps4, are required for cytokinesis, viral budding, protecting viral genomes from degradation, exosome secretion, receptor shedding on microvesicles, assembly of nuclear pore complexes, cholesterol transport and plasma membrane wound repair (Barajas et al, 2014;Choudhuri et al, 2014;Du et al, 2013;de Gassart et al, 2004;Jimenez et al, 2014;Morita, 2012;Nabhan et al, 2012;Tang, 2012;Webster et al, 2014).…”
Section: Introductionmentioning
confidence: 99%